2017
DOI: 10.1159/000461569
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Viral Exposure on P-Glycoprotein Function in the Mouse Fetal Blood-Brain Barrier

Abstract: Background/Aims: Viral infection during pregnancy is known to affect the fetal brain. The toll-like receptor (TLR)-3 is a pattern recognition receptor activated by viruses known to elicit adverse fetal neurological outcomes. The P-glycoprotein (P-gp) efflux transporter protects the developing fetus by limiting the transfer of substrates across both the placenta and the fetal blood-brain barrier (BBB). As such, inhibition of P-gp at these blood-barrier sites may result in increased exposure of the developing fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
6
24
0
Order By: Relevance
“…Some studies have shown that chemoresistance may be attributed to expression of the multidrug resistance gene ( MDR1 ) and its encoded protein P-gp, which has been found to reduce drug uptake [28]. In our study, after treatment of A549/DDP cells with AA alone or with a combination of DDP with AA, the expression of MDR1 (P-gp) significantly decreased.…”
Section: Discussionmentioning
confidence: 48%
“…Some studies have shown that chemoresistance may be attributed to expression of the multidrug resistance gene ( MDR1 ) and its encoded protein P-gp, which has been found to reduce drug uptake [28]. In our study, after treatment of A549/DDP cells with AA alone or with a combination of DDP with AA, the expression of MDR1 (P-gp) significantly decreased.…”
Section: Discussionmentioning
confidence: 48%
“…A decrease in P-gp protein expression in PTDC may be associated with fetal accumulation of P-gp substrates, such as endogenous and synthetic glucocorticoids, estrogens and pro-inflammatory compounds. This possibility is supported by the evidence that LPS and polyI:C inhibited P-gp activity and increased fetal drug exposure in pregnant mice [8, 54]. P-gp also transports important classes of drugs such as angiotensin receptor blockers, antibiotics, antiepileptics, antihistamines, antiretrovirals, NSAIDs and statins1.…”
Section: Discussionmentioning
confidence: 93%
“…C57BL/6 mice exposed to sublethal (foetal) LPS in mid-pregnancy, exhibited impaired placental P-gp activity, 18 while polyinosinic:polycytidylic acid (PolyI:C, a viral mimic) had no effect on placental P-gp activity. 36 Human first-trimester placentae exposed to lipopolysaccharide (LPS, a bacterial antigen) exhibited decreased P-gp/ABCB1 and BCRP/ABCG2 levels. 37 In contrast, human chorioamnionitis in 2nd trimester, often resulting from polymicrobial infection, 38 resulted in decreased P-gp levels but elevated BCRP expression.…”
Section: Discussionmentioning
confidence: 99%